The concept of emotional intelligence and the problem of its assessment - Remeikaitė, Irina; Lekavičienė, Rosita (Psichologija, 2002)
The concept of emotional intelligence is rather new in Lithuania and most often mentioned only in popular magazines. This article tries to systematize the variety of existing concepts of emotional intelligence by comparing emotional intelligence with other similar concepts - social intelligence, rational intelligence etc. In general there are two main theories defining emotional intelligence. One approach (Mayer, et al.) defines emotional intelligence only as ability, and the other (Bar-On, Goleman) includes personality traits into the concept of emotional intelligence too. Commonly emotional intelligence is defined as ability in witch individual traits are more or less involved, that helps to process emotional information - to identify and recognize emotions and their meaning, assimilate and control them so to facilitate the reasoning. This article considers how to estimate emotional intelligence of individuals, not only their attitudes towards it, and also introduces best known methodologies (Bar-On Emotional Intelligence Inventory, Multifactoral Emotional Intelligence scale, I. Jerabek EI test etc.) and their validity questions. It also analyses relationship between emotional intelligence and personality traits, age and sex factors. It gives an opinion on how the emotional intelligence could be developed.